Teachers’ Perception and Experiences on Artificial Intelligence (AI) Integration in English Language Teaching and Learning - Ghimire, Puna Ram; Neupane, Bharat Prasad (Lumbini Journal of Language and Literature, 2024)
This study reports English language teachers’ perceptions and experiences of integrating artificial intelligence (AI) and the professional development needs for its effective integration subscribing to Vygotsky's Zone of Proximal Development (ZPD) as a theoretical lens. We employed narrative inquiry research method and semi-structured interviews to elicit the experiences of three secondary level English teachers in Butwal Sub-metropolitan City of the Rupandehi district. The research questions focused on teachers' perceptions and experiences of AI integration and their professional development needs. The findings revealed that teachers recognized the potential of AI to enhance personalized learning and instructional efficiency but face significant challenges, including technological proficiency, training, and ethical considerations. The implications of this research extended to educators and policymakers to address the digital divide and ensure equitable access to AI technologies in education to create more effective and personalized learning environments.